Social audit of expenditure on the internally displaced persons due to the armed conflict in the East of Ukraine: current necessity - Hladii, I. O.; Kuznetsova, Svitlana; Dziuba, O. M.; Maister, L. A.; Govorko, O. V. (Університет банківської справи, 2021)
The globalization of economic relations of the XXI century led to the realization that human resources are the driving force in the development of the stability of the state. A great number of internally displaced persons that appeared was a challenge for Ukraine because the establishment and protection of human rights and freedoms are the main responsibility of the state. This is why the need to form a system of social cost audit on the internally displaced persons due to the armed conflict in the east of Ukraine is a priority in order to optimize the ways of establishing social consensus by taking concerted actions to develop human resources. The strategic focus of the social audit is to become a crucial factor for implementing the main principles of social partnership in regulating social and labour relations and carrying out the strategy of the financial encouragement of internally displaced persons due to the armed conflict in the east of Ukraine. The problems and needs of internally displaced persons were discussed by many researchers. The issue of improving the system of the social audit was described in the works of A. Liubenko, V. Rysin, V. Pikhotskyi, M. Bukovynska, O. Hnatiuk, O. Ponomarenko, S. Sachenko, F. Fukuiama, etc. As the analysis of the studies conducted by scientists implies, the urgent matter emerging in the current realities was not outlined in their works. Little attention was given to improving the efficient analysis system of social risks of either enterprise or state by implementing the social audit. The study aims at examining the consistent patterns of allocation of funds of pilot projects total cost between the number of registered internally displaced persons and their families in Ukraine using the social audit as the foundation for carrying out the strategy of the financial encouragement of internally displaced persons while they are socializing in new areas. The study analyzed the funds allocated for the implementation of pilot projects aiming at the protection of human rights and legitimate interests violated by the armed conflict in the east of Ukraine and/or temporary occupation of the part of Ukraine. The study of the consistent patterns of allocation of funds of pilot projects total cost between the number of registered internally displaced persons and their families in Ukraine was carried out. It was revealed that increasing the number of registered persons does not influence the allocation of funds between them. It emphasizes the importance of examining the factors of these phenomena, which can be provided by the social audit of allocation of funds on a national scale. The need to carry out the social audit using participatory principle is stressed.

Глобалізація економічного мислення ХXI століття призвела до усвідомлення того, що людські ресурси є вирішальними у процесі досягнення стійкості розвитку держави. Поява значної кількості внутрішньо переміщених осіб стала викликом для України, оскільки утвердження і забезпечення прав і свобод людини є головним обов’язком держави. Саме тому питання необхідності побудови системи соціального аудиту витрат на внутрішньо переміщених осіб унаслідок збройного конфлікту на Сході України стає пріоритетним у напрямі оптимізації шляхів досягнення соціального консенсусу через ужиття узгоджених заходів з розвитку людських ресурсів. Стратегічна направленість соціального аудиту покликана стати важливим чинником практичної реалізації основних принципів соціального партнерства в регулюванні соціально-трудових відносин і побудови стратегії фінансового заохочення внутрішньо переміщених осіб унаслідок збройного конфлікту на Сході України. Проблемам і потребам внутрішньо переміщених осіб у своїх дослідженнях приділяли увагу багато дослідників. Питанням налагодження системи соціального аудиту присвячено роботи А. Любенка, В. Рисіна, В. Піхоцького, М. Буковинської, О. Гнатюка, Р. Пономаренко, С. Саченко, Ф. Фукуями та інших. Аналіз проведених досліджень науковців засвідчив, що переважно їхні праці не висвітлюють нагального питання, що постало в сучасних реаліях. Налагодженню ефективної системи аналізу чинників соціальних ризиків як підприємства, так і держави шляхом запровадження соціального аудиту не приділено належної уваги. Метою статті виступила об’єктивна необхідність у дослідженні закономірностей розподілу коштів загальної вартості пілотних проєктів між кількістю облікованих внутрішньо переміщених осіб та їхніх сімей на території України із застосуванням прийомів соціального аудиту як основи побудови стратегії фінансового заохочення внутрішньо переміщених осіб у процесі їхньої максимальної соціалізації на нових територіях. У дослідженні проведено аналіз коштів, виділених на реалізацію пілотних проєктів, які направлені на захист прав і законних інтересів осіб, що порушені внаслідок збройного конфлікту та/або тимчасової окупації частини території України. Проведено дослідження закономірностей розподілу коштів загальної вартості пілотних проєктів між кількістю облікованих внутрішньо переміщених осіб і сімей на території України. Виявлено, що збільшення кількості облікованих осіб не впливає на розподіл коштів між ними і це говорить про необхідність дослідження причин цих явищ, що в загальнодержавному масштабі може зробити соціальний аудит розподілу досліджуваних коштів. Доведено необхідність проведення соціального аудиту за принципом партисипативності. Проведення соціального аудиту витрат на внутрішньо переміщених осіб дозволить отримати об’єктивну інформацію про соціально-економічні відносини; виявити рівень соціальної напруженості та своєчасно вжити превентивні заходи; ефективно регулювати соціально-економічні відносини за допомогою соціального партнерства.
Соціальний аудит витрат на внутрішньо переміщених осіб унаслідок збройного конфлікту на Сході України: необхідність сьогодення
Keywords: social audit; internally displaced persons; costs; communities; analysis; participatory principle; plan of the social audit; економіка; громади; аналіз; принцип партисипативності; людські ресурси; фінанси